Teuvincenone F Suppresses LPS-Induced Inflammation and NLRP3 Inflammasome Activation by Attenuating NEMO Ubiquitination - Zhao, Xibao; Pu, Debing; Zhao, Zizhao; Zhu, Huihui; Li, Hongrui; Shen, Yaping; Zhang, Xingjie; Zhang, Ruihan; Shen, Jianzhong; Xiao, Weilie; Chen, Weilin (Frontiers in Pharmacology, 2017)
Inflammation causes many diseases that are serious threats to human health. However, the molecular mechanisms underlying regulation of inflammation and inflammasome activation are not fully understood which has delayed the discovery of new anti-inflammatory drugs of urgent clinic need. Here, we found that the natural compound Teuvincenone F, which was isolated and purified from the stems and leaves of Premna szemaoensis, could significantly inhibit lipopolysaccharide (LPS)–induced pro-inflammatory cytokines production and NLRP3 inflammasome activation. Our results showed that Teuvincenone F attenuated K63-linked ubiquitination of NF-κB-essential modulator (NEMO, also known as IKKγ) to suppress LPS-induced phosphorylation of NF-κB, and inhibited mRNA expression of IL-1β, IL-6, TNF-α and NLRP3. In addition, we found that decreased NLRP3 expression by Teuvincenone F suppressed NLRP3 inflammasome activation and IL-1β/IL-18 maturation. In vivo, we revealed that Teuvincenone F treatment relieved LPS-induced inflammation. In conclusion, Teuvincenone F is a highly effective natural compound to suppress LPS-induced inflammation by attenuating K63-linked ubiquitination of NEMO, highlighting that Teuvincenone F may be a potential new anti-inflammatory drug for the treatment of inflammatory and NLRP3 inflammasome-driven diseases.